Carvacrol is highly disruptive against coagulase-negative staphylococci in in vitro biofilms - Gaio, Vânia Silva (2017)
Aim: To evaluate the antimicrobial activity of carvacrol against stationary-phase planktonic and biofilm cells of coagulase-negative staphylococci and comparison to traditional antistaphylococcal antibiotics. MATERIALS & METHODS: The antimicrobial effect of carvacrol and antibiotics against planktonic and biofilm cells were assessed through quantification of the number of culturable and/or viable cells. Confocal laser scanning microscopy was used to evaluate the effect of carvacrol on the biofilm structure. RESULTS: A concentration of 4 mM of carvacrol demonstrated a potent antimicrobial effect, vastly superior than ciprofloxacin, rifampicin, gentamicin and vancomycin, both in planktonic and biofilm cells. CONCLUSION: Carvacrol is a potential antimicrobial agent, which applicability for the prevention and/or treatment of coagulase-negative staphylococci biofilm-associated infections is worthwhile investigating in more detail.